Psychological Factors Affecting Student’s Anxiety Towards Accounting Modules In Financial And Banking Science Department And Accounting Department At Faculty Of Economics In Tishreen University - حاتم اياد; نصار باسل (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study examined psychological factors affecting student’s anxiety towards accounting modules. These factors include fear, desire, incapability and self-confidence. A pilot study was conducted by distributing 300 questionnaire to students in Financial and Banking Science department and Accounting department at Faculty of Economics in Tishreen University over the period 2018-2019. Only 225 questionnaire was qualified to be included in the sample. The results showed that students feel anxious towards accounting modules and this was confirmed by the results of T-Test. Also, the results implied a positive impact of fear and incapability on anxiety level as well as a negative impact of self-confidence and desire on anxiety level. Besides, the anxiety level seemed to vary among Accounting modules and majors. On the other hand, there was no statistical difference between students of third and fourth years regarding anxiety towards accounting modules.